Persepsi Pustakawan Perguruan Tinggi Agama Islam Negeri di Indonesia terhadap Artificial Intelligence - Rodliyah, Ummi (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Library development is inseparable from technological developments, and one of the latest innovations that is gaining attention is artificial intelligence (AI). Librarian as profession is one of the pillars of library development, so it is important to study how they perceive and respond to AI developments. This research uses a quantitative design with a survey approach. The target of this research is the librarians of Universitas Islam Indonesia who are members of the WhatsApp Group of the Association of Islamic Higher Education Libraries (APPTIS) with 316 members as the population. The survey used Google form media whose links were distributed through the GWA from May 28 to June 2, 2024. There were 75 respondents from 15 provinces in Indonesia consisting of UIN, IAIN, and STAIN. The survey results show that 44% of respondents have a good perception of AI and make the use of AI in daily life a habit. While 56% have not made the use of AI a daily habit. The survey also found that Youtube is the most popular application used among librarians, followed by Google products (Google Scholar, Google Translate) which are more preferred than ChatGPT. Likewise, Google Trend is more preferred than elicit, litmaps and SciSpace. The survey also shows that librarians in Central Java are more likely to deliver AI materials to users than librarians in other regions. The results of the analysis also show that there is no difference in the level of perception based on the librarian's job title, institution status, or region.